Healthcare Providers' Knowledge of Diets and Dietary Advice. Issue 9 (September 2015) - Arora, Sonali; Atreya, Auras R.; Bernstein, Adam M.; Kleppel, Reva; Friderici, Jennifer; Schramm, Sarah; Lagu, Tara; Rothberg, Michael B.
<x xml:space="preserve">Abstract</x> Objectives Little is known about healthcare providers' knowledge of dietary evidence or about what dietary advice providers offer to patients. The objective of our study was to determine which diets providers recommended to patients and providers' beliefs about the evidence behind those recommendations. Methods This was a 22-question cross-sectional survey conducted between February 2013 and September 2013, in 45 ambulatory practices within two health systems. Attending physicians, housestaff, and advanced practitioners in internal medicine, medicine-pediatrics, family medicine, cardiology, and endocrinology practices were audited. Providers' attitudes, perceptions, and beliefs about diet modification were collected. Knowledge scores were constructed based on the number of correct responses to specific questions. Results Of 343 provider responses, largely from primary care specialties (n = 3027, 90%), the top dietary recommendations were low-salt diet (71%) for hypertension, low-carbohydrate diet (64%) for uncontrolled diabetes mellitus, low saturated fat diet (73%) for dyslipidemia, low-calorie diet (72%) for obesity, and low saturated fat diet (63%) for coronary heart disease. Providers believed that 51% of diet recommendations were supported by randomized trial evidence when they were not. Respondents' overall knowledge of randomized trial evidence for dietary interventions was low (mean [standard deviation] knowledge score 44.3% [22.4%], range 0.0%–100.0%). The survey study from two health systems, using a nonvalidated survey tool limits external and internal validity. Conclusions Providers report recommending different diets depending on specific risk factors and generally believe that their recommendations are evidence based. Substantial gaps between their knowledge and the randomized trial evidence regarding diet for disease prevention remain.